Connecting Freedom of Association and the Right to Strike: European Dialogue with the Ilo and Its Potential Impact - Novitz, Tonia (Canadian Labour & Employment Law Journal, 2009)
The International Labour Organization’s supervisory bodies responsible for assessing state compliance with “freedom of association” have established an extensive jurisprudence on the right to strike. This jurisprudence is based on their interpretation of the ILO Constitution and various key ILO conventions concerning the right to organize and collective bargaining, in both the private and the public sector. Since the end of the Cold War, the employer lobby within the ILO has increasingly tried to undermine this aspect of ILO jurisprudence, so as to deny that there is any necessary link between freedom of association and the right to take industrial action. This pressure has come at a time when ILO norms are beginning to receive greater attention and respect, and are being applied in the human rights jurisprudence of other legal systems, including those of Canada and Europe. In 2007, the European Court of Justice for the first time explicitly recognized a right to strike, referring to ILO Convention 87 as a source of this entitlement, but limited it by imposing a proportionality requirement on its exercise. In 2009, the European Court of Human Rights indicated for the first time that the right to strike was implicit in Article 11 of the European Convention on Human Rights, again in reliance on ILO standards. This paper compares and contrasts those cases, investigating the extent to which European recognition of a right to strike can serve to reinforce or undermine ILO standards. The paper also considers the more general implications of these developments for Canadian human rights jurisprudence.